2020
DOI: 10.18488/journal.aefr.2020.109.1012.1027
|View full text |Cite
|
Sign up to set email alerts
|

Internal Audit Function Characteristics and the Quality of Internal Control Systems: Moderating the Effect of Enterprise Resource Planning System Maturity

Abstract: The aim of this study is to investigate the relationship between the internal audit function (IAF) (independence and competence) and the quality of internal control systems (ICSQ). It also aims to assess the moderating role of the maturity of enterprise resource planning (ERP) on these relationships. Using data from 98 Saudi Arabian small and medium-sized enterprises (SMEs) that have implemented an ERP system, this paper uses a Structural Equation Model to examine the hypotheses. In particular, the Partial Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…From these articles, four studies investigate the mediating effect of various factors such as job burnout (Shbail et al, 2018), IA quality (Bshayreh et al, 2019; Mustafa & Al-Nimer, 2018), job satisfaction (Obeid et al, 2017). Limited studies (four studies) have also investigated the moderating impact of several factors like the maturity of enterprise resource planning (Shaiti & Al-Matari, 2020), IA mechanisms (E. M. Al-Matari & Hussein Mgammal, 2019), external auditor’s size (Khlif & Samaha, 2016), and task complexity (Alqudah et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From these articles, four studies investigate the mediating effect of various factors such as job burnout (Shbail et al, 2018), IA quality (Bshayreh et al, 2019; Mustafa & Al-Nimer, 2018), job satisfaction (Obeid et al, 2017). Limited studies (four studies) have also investigated the moderating impact of several factors like the maturity of enterprise resource planning (Shaiti & Al-Matari, 2020), IA mechanisms (E. M. Al-Matari & Hussein Mgammal, 2019), external auditor’s size (Khlif & Samaha, 2016), and task complexity (Alqudah et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that very limited work considered the interaction of different factors in explaining the complexity of the IAFs and their influence by including moderating or mediating variables (E. M. Al-Matari & Hussein Mgammal, 2019; Alqudah et al, 2019; Baatwah et al, 2021; Shaiti & Al-Matari, 2020). Hence, future studies can take a step further in this direction and consider the interrelation between various factors in exploring the role of IA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations